2006
DOI: 10.1007/s11284-006-0308-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microenvironmental heterogeneity on the seed‐to‐seedling process and tree coexistence in a riparian forest

Abstract: In a temperate riparian forest, the effects of substrate types, canopy gaps and conspecific seedfall density were investigated on the seed-to-seedling process for the five dominant species (Aesculus turbinata, Fagus crenata, Acer mono, Pterocarya rhoifolia and Cercidiphyllum japonicum). Densities of seedfall and subsequent seedling recruits were measured in the stand over a period of 6 years. A model assuming that local density of seedling recruits is proportional to seedfall density in the preceding year sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 41 publications
1
13
0
1
Order By: Relevance
“…This result is compatible with the assumption of previous studies that the TND during early life stages takes the first priority (e.g., Shibata and Nakashizuka 1995;Masaki et al 2005), and emphasizes importance of the regeneration niche (Grubb 1977). Many previous studies found interspecies differences in response with recruitment rate to topography, but these studies failed to completely explain distribution patterns of large trees by the detected species-specific responses (e.g., Webb and Peart 2000;Nagamatsu et al 2002;Masaki et al 2007). This mismatch is attributable to two spatial processes: dispersal limitation and density-dependent mortality.…”
Section: Tnd At Early and Later Life-history Stagessupporting
confidence: 90%
“…This result is compatible with the assumption of previous studies that the TND during early life stages takes the first priority (e.g., Shibata and Nakashizuka 1995;Masaki et al 2005), and emphasizes importance of the regeneration niche (Grubb 1977). Many previous studies found interspecies differences in response with recruitment rate to topography, but these studies failed to completely explain distribution patterns of large trees by the detected species-specific responses (e.g., Webb and Peart 2000;Nagamatsu et al 2002;Masaki et al 2007). This mismatch is attributable to two spatial processes: dispersal limitation and density-dependent mortality.…”
Section: Tnd At Early and Later Life-history Stagessupporting
confidence: 90%
“…) and fine‐scale habitat heterogeneity has been previously shown to regulate community assembly processes (Palmer & Dixon ; McAlpine & Drake ; Masaki et al. ; Firth & Crowe ).…”
Section: Discussionmentioning
confidence: 99%
“…During these procedures, only a portion of trees is removed, and the overall stand abiotic environment is not greatly altered. Therefore, partial removal of trees can enhance local light availability and create physical environments similar to natural gaps that are essential for seedling survival (Augspurger, 1984;Brokaw & Busing, 2000;Masaki et al, 2007). In addition, the presence of understory vegetation may reduce seedling survival by reducing light availability or increasing competition between seedlings and understory vegetation (Leck et al, 2008).…”
Section: Historical Backgroundmentioning
confidence: 99%